Preventing loss of independence through exercise (PLIÉ) for persons with dementia: A randomized, controlled trial: Dementia care research: Behavioral interventions. (7th December 2020) - Barnes, Deborah E; Lee, Jennifer Ann; Chesney, Margaret A; Yaffe, Kristine; Abrams, Gary; Nicosia, Francesca M; Martinez, Steven; Ordonez, Cherry; Woo, Michele; Boscardin, W John; Mehling, Wolf
Abstract: Background: Preventing Loss of Independence through Exercise (PLIÉ) is an integrative group movement program for people living with dementia that combines exercises to maintain daily function with mindful body awareness and social engagement. We performed a randomized, controlled trial to examine PLIÉ's effects on physical, cognitive, and social/emotional outcomes using quantitative and qualitative methods. Methods: Study participants were persons with mild‐to‐moderate dementia (Clinical Dementia Rating: 0.5, 1 or 2) and their caregivers recruited from 4 adult day center study sites and surrounding communities. Participants were randomly assigned to immediate or delayed start in PLIÉ classes (1 hour, 2‐3 days/week, 18 weeks) at each site. Quantitative outcome data were collected at 0, 18 and 36 weeks by blinded assessors. Our primary outcomes in participants were physical performance, cognitive function, and self‐rated quality of life. Secondary outcomes included caregiver‐reported independence, behaviors, and fall concern for participants and self‐rated mood, burden, and feelings about caregiving for themselves. Caregivers also received anonymous evaluation surveys with satisfaction ratings (5‐point Likert) and open‐ended questions about PLIÉ‐related changes in participants. We used mixed effects linear models adjusting for baseline differences for quantitative data and content analysis for qualitative data. Results: We enrolled 88 participant/caregiver dyads, of whom 68 (77%) completed the 18‐week assessment, 55 (62%) completed the 36‐week assessment, and 47 (53%) returned evaluation surveys. Participants were 80±8 years old, 67% men, 60% Veterans and 86% non‐Hispanic White; caregivers were 67±14 years old, 83% women and 84% non‐Hispanic White. There were no significant differences between groups over time in primary or secondary quantitative outcomes, with the exception of increased caregiver burden in the immediate‐ vs. delayed‐start group (p=0.03). However, satisfaction ratings among survey respondents were high (mean: 4.5±0.9), and caregivers reported qualitative improvements in participants in 4 domains: psychological, physical, cognitive, and social. In addition, many caregivers reported improvements in multiple domains (Table). Conclusion: Although there was no overall benefit in quantitative measures commonly used in dementia studies, a subset of caregivers reported qualitative benefits in program participants in response to PLIÉ. More sensitive measures may be needed to fully evaluate PLIÉ's effects.